2022
DOI: 10.3389/fenvs.2022.899571
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Functional and Taxonomic Phytoplankton Diversity to Environmental Gradients in Subtropical and Tropical Reservoirs

Abstract: Understanding the influence of environmental conditions on biodiversity is a major task in ecology. We investigated how phytoplankton taxonomic (TD) and functional (FD) diversities vary with environmental factors in eight subtropical and tropical reservoirs. We hypothesized that i) environmental variables affect phytoplankton TD and FD; ii) FD provides better relationships to environmental changes than TD, and; iii) indices based on biomass are better related to the environment than those based on identities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Several studies have investigated the patterns and mechanisms of phytoplankton diversity using different indices [77,78] and in terms of functional diversity compared to taxonomic diversity. Differences in functionality have been distinguished from morphological traits [79,80]; the majority of the studies on phytoplankton functional diversity have been based on the presence or absence of identities in terms of species richness [81,82], and very few have been conducted on functional groups defined by body size and the basis of abundance-or biovolumebased functional diversity [83][84][85]. The South-Western Pacific Ocean and Indo-Pacific Ocean regions exhibited the highest similarity in terms of phytoplankton taxa composition and abundance, while the South-Western Atlantic Ocean region was the most dissimilar compared to the others.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the patterns and mechanisms of phytoplankton diversity using different indices [77,78] and in terms of functional diversity compared to taxonomic diversity. Differences in functionality have been distinguished from morphological traits [79,80]; the majority of the studies on phytoplankton functional diversity have been based on the presence or absence of identities in terms of species richness [81,82], and very few have been conducted on functional groups defined by body size and the basis of abundance-or biovolumebased functional diversity [83][84][85]. The South-Western Pacific Ocean and Indo-Pacific Ocean regions exhibited the highest similarity in terms of phytoplankton taxa composition and abundance, while the South-Western Atlantic Ocean region was the most dissimilar compared to the others.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that planktonic plant diversity was largely positively correlated with dissolved oxygen, water temperature, and total nitrogen. Studies have shown that temperature is a primary ecological driver of planktonic plant diversity, with increasing temperatures affecting plant growth and reproduction, thereby promoting increased biological diversity by occupying different ecological niches [28]. The dissolved oxygen content in water affects the distribution and abundance of planktonic organisms, thereby influencing the overall community's taxonomic diversity.…”
Section: Discussionmentioning
confidence: 99%